Cover Feature: The Bacterial Extracellular Matrix Protein TapA Is a Two‐Domain Partially Disordered Protein (ChemBioChem 3/2019). (11th January 2019) - Abbasi, Razan; Mousa, Reem; Dekel, Noa; Amartely, Hadar; Danieli, Tsafi; Lebendiker, Mario; Levi‐Kalisman, Yael; Shalev, Deborah E.; Metanis, Norman; Chai, Liraz
Abstract : The cover feature picture shows the sequence of the protein TapA along a colored ruler, depicting the degree of disorder: red being structured and blue being disordered residues. The bottom cord shows that the structure of TapA is environment‐dependent. The C‐terminal domain remains disordered, whereas the N‐terminal domain (red tangle) gains structure upon a temperature increase or the addition of liposomes (yellow balls in the fore‐ and background). More information can be found in the communication by L. Chai et al. on page 355 in Issue 3, 2019 (DOI: 10.1002/cbic.201800634 ).